+0  
 
-2
38
1
avatar

If we express 2x^2 + 6x + 11 in the form a(x - h)^2 + k, then what is h?

 Jun 2, 2022
 #1
avatar+280 
+4

a(x^2 - 2xh + h^2) + k = 2x^2 + 6x + 11

ax^2 - 2axh + ah^2 + k = 2x^2 + 6x + 11. 

a = 2. 

2x^2 - 4xh + 2h^2 + k = 2x^2 + 6x + 11

h = 3/2

I already got the answer but I'm going to keep going for k. 

9/2 + k = 11. k = 6.5. 

k = 13/2

the form should be 2(x + 3/2)^2 + 13/2

 

 

 

 

 

edit: btw I already helped like 5 people about this topic.

 Jun 3, 2022
edited by hipie  Jun 3, 2022

18 Online Users

avatar
avatar